Design and implementation of a parent guide for coaching teen drivers. (September 2018) - Buckley, Lisa; Shope, Jean T.; Zakrajsek, Jennifer S.; Goldstick, Jason E.
Abstract: Introduction: Teens beginning to drive independently are at significant increased risk of motor-vehicle crashes relative to their other life stages. There is, however, little guidance for parents as to how best to supervise learning to drive. Method: This study sought to undertake an informed approach to development and implementation of a Parent Guide . We included a multi-stage development process, using theory, findings from a Delphi-study of young driver traffic-safety experts, and parent focus groups. This process informed the development of a Guide that was then evaluated for feasibility and acceptability, comparing a group that received the Guide with a control group of parent and teen dyads. Both members of the dyads were surveyed at baseline, again at the approximate time teens would be licensed to drive independently (post-test), and again three months later. Results: We found no difference in the proportion of teens who became licensed between those given the new Guide and control teens (who received the state-developed booklet); that is the Guide did not appear to promote or delay licensure. Teens in the Guide group reported that their parents were more likely to use the provided resource compared with control teens. Responses indicated that the Parent Guide was favorably viewed, that it was easy to use, and that the logging of hours was a useful inclusion. Parents noted that the Guide helped them manage their stress, provided strategies to keep calm, and helped with planning practice. In contrast, control parents noted that their booklet helped explain rules. Among licensed teens there was no significant difference in self-reported risky driving at the three-month follow-up. We discuss the challenges in providing motivation for parents to move beyond a set number of practice hours to provide diversity of driving practice. Highlights: Providing a Parent Guide booklet did not appear to promote or delay licensure. More teens reported that their parents used the Guide than controls receiving the state booklet. The Guide was favorably viewed and easy to use. The Guide reportedly helped with managing stress and planning practice. There are challenges in recruiting and motivating parents to engage.